The role of duplication in the expression of a variable surface glycoprotein of Trypanosoma brucei - Young, J.R.; Turner, M.J.; Williams, R.O. (Wiley, 1984)
The variable surface glycoprotein (VSG) genes of Trypanosoma brucei have been classified into two groups depending upon whether or not duplication of the genes is observed when they are expressed. We report here the observation of duplication apparently linked to espression of the ILTaT 1.3 gene in the ETaR 1 trypanosome stock. In the ILTaR 1 stock, expression of the ILTaT 1.3 VSG did not involve a new duplication, but instead activation of a preexisting gene copy that had been apparently generated earlier by a duplication event analogous to that directly observed in the ETaR 1 trypanosomes. The results suggest that the well‐characterised gene duplications found with other VSG genes are common to all VSG genes but are not directly responsible for controlling expression. All currently available data can be accomodated by a model that assumes that gene duplication and replacement occurs independently of antigenic switching.